2019
DOI: 10.1136/bmjopen-2018-026632
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of acupuncture with Doin therapy for chronic neck pain: a study protocol for a multicentre, randomised controlled clinical trial

Abstract: IntroductionDoin therapy is a manual therapy used in Korean rehabilitation medicine. Recently, the use of acupuncture with Doin has increased in clinics and clinical trials have demonstrated its effects. However, well-designed studies examining the efficacy and cost-effectiveness of acupuncture with Doin therapy are rare.Methods and analysisThis multicentre, assessor-blinded, randomised controlled trial with two parallel groups aims to evaluate the clinical effects and cost-effectiveness of acupuncture with Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Based on a previous study, the intervention group will receive a 12-week exercise program with nutritional support, whereas the control group will only receive educational materials without intervention for 12 weeks [32].…”
Section: Detailed Description Of the Combined Exercise And Nutrition ...mentioning
confidence: 99%
“…Based on a previous study, the intervention group will receive a 12-week exercise program with nutritional support, whereas the control group will only receive educational materials without intervention for 12 weeks [32].…”
Section: Detailed Description Of the Combined Exercise And Nutrition ...mentioning
confidence: 99%
“…Patients are required to perform local exercises with acupuncture needles in the distal limbs. [18] Motion style acupuncture treatment (MSAT) as one of the complementary and alternative medical therapies for acute lumbar sprain, several studies have shown that it could improve acute lumbar sprain symptoms by relieving pain and improving lumbar activity. [19][20] According to the theory of traditional Chinese medicine, which relieves pain by removing the obstruction to the ow of Qi.…”
Section: Introductionmentioning
confidence: 99%
“…Motion style acupuncture treatment (MSAT) is a method combining acupuncture treatment with Doin therapy [ 18 ]. In MSAT, the traditional acupuncture treatment is followed by passive or active movement of the patient’s body while the acupuncture needles are inserted.…”
Section: Introductionmentioning
confidence: 99%